Characterization of patients with low health literacy using warfarin (Research, Society and Development, 2023)
Introduction: Health literacy (HL) is considered a factor that interferes with warfarin treatment, since the literature indicates an association between low understanding of the treatment and inadequate control of oral anticoagulation. The study aimed to characterize patients with low functional health literacy in an anticoagulation clinic in Minas Gerais. Methodology: The work was carried out at the anticoagulation outpatient clinic at the UFMG clinic hospital. Participants signed the consent form, respecting the precepts of bioethics. Individuals with inadequate TTR values (TTR